Medication errors in prescription and administration in critically ill patients. (24th February 2020) - Suclupe, Stefanie; Martinez‐Zapata, Maria Jose; Mancebo, Jordi; Font‐Vaquer, Assumpta; Castillo‐Masa, Ana María; Viñolas, Iris; Morán, Indalecio; Robleda, Gemma
Abstract: Aim: To determine the prevalence and magnitude of medication errors and their association with patients' sociodemographic and clinical characteristics and nurses' work conditions. Design: An observational, analytical, cross‐sectional and ambispective study was conducted in critically ill adult patients. Methods: Data concerning prescription errors were collected retrospectively from medical records and administration errors were identified through direct observation of nurses during drug administration. Those data were collected between April and July 2015. Results: A total of 650 prescription errors were identified for 961 drugs in 90 patients (mean error 7[ SD 4.1] per patient) and prevalence of 47.1% (95% CI 44–50). The most frequent error was omission of the prescribed medication. Intensive care unit stay was a risk factor associated with omission error (OR 2.14; 1.46–3.14: p < .01). A total of 294 administration errors were identified for 249 drugs in 52 patients (mean error 6 [ SD 6.7] per patient) and prevalence of 73.5% (95% CI 68–79). The most frequent error was interruption during drug administration. Admission to the intensive care unit (OR 0.37; 0.21–0.66: p < .01), nurses' morning shift (OR 2.15; 1.10–4.18: p = .02) and workload perception (OR 3.64; 2.09–6.35: p < .01) were risk factors associated with interruption. Conclusions: Medication errors in prescription and administration were frequent. Timely detection of errors and promotion of a medication safety culture are necessary to reduce them and ensure the quality of care in critically ill patients. Impact: Medication errors occur frequently in the intensive care unit but are not always identified. Due to the vulnerability of seriously ill patients and the specialized care they require, an error can result in serious adverse events. The study shows that medication errors in prescription and administration are recurrent but preventable. These findings contribute to promote awareness in the proper use of medications and guarantee the quality of nursing care. Abstract : 目的: 确定用药失误的发生率、程度及其与患者社会人口学、临床特征以及护士工作条件之间的关系。 设计: 对成年危重患者进行观察性、分析性、横向和双向性研究。 方法: 从病历中回顾性收集处方错误相关数据, 并通过对护士在用药期间的直接观察, 发现用药失误。此类数据于2015年4月至7月期间收集。 结果: 在90例患者使用的961种药物中共发现有650个处方错误(平均错误率7【SD 4.1】), 发生率为47.1%(95%CI 44‐50)。最为常见的一类错误是漏开处方药。重症监护病房住院时间是导致出现漏开失误的一大相关风险因素(OR2.14;1.46‐3.14: p < .01)。52例患者使用的249种药物中共发现有294个用药失误(平均失误率为6【SD 6.7】), 发生率为73.5%(95%CI 68‐79)。最为常见的一类失误是用药期间出现中断。入住重症监护病房(OR0.37;0.21–0.66: p < .01)、护士早班交接(OR2.15;1.10–4.18: p = .02)以及工作负荷感知(OR3.64;2.09–6.35: p < .01)为导致用药中断的相关风险因素。 结论: 处方用药错误频发。及时发现错误并倡导药物安全知识, 对减少错误、保证危重患者护理质量具有重要意义。 影响: 在重症监护病房, 药物错误经常发生, 但并非总是得以发现。由于重病患者身体脆弱, 且需特殊护理, 此类错误可能导致严重的不良事件。研究表明, 处方用药错误虽频频发生, 但可予以预防。此等发现有助于提高人们对正确使用药物的认识, 保证护理质量。